Trapped Below: Abdominal Pseudocysts Associated With Ventriculoperitoneal Shunts in Coccidioidal Meningitis - Sivasubramanian, Geetha (Open forum infectious diseases, 2025)
Ventriculoperitoneal (VP) shunts are the mainstay for cerebrospinal fluid diversion in patients with refractory coccidioidal meningitis (CM)-associated hydrocephalus. Abdominal pseudocysts (APCs), an uncommon but known complication of distal shunt catheters, have not been well described in CM. We conducted a retrospective study of 124 patients with CM who underwent VP shunt placement between 2010 and 2024. APCs occurred in 21 patients (17%), with most presenting with symptoms of shunt malfunction rather than abdominal complaints. This incidence is notably higher than previously reported in patients with hydrocephalus due to other etiologies. Evidence of active Coccidioides infection was present in 71% of patients. Imaging typically revealed fluid collections at the distal catheter tip, and most patients underwent surgical intervention targeting the distal shunt. Despite intervention, recurrent shunt failures occurred in a substantial proportion. These findings add to the limited literature on APCs in CM and may inform future research into their presentation, contributing factors, and management.